Comprehensive course on entrepreneurship and the future entrepreneurs among the University of the Philippines in the Visayas - College of Management (UPV-CM) students - Alvañez, Maria Antonia Fatima B.; Cinco, Francis P.; Constantino, Rommel; Diosaban, Victor B. (1993.)
This study was undertaken to determine if there is a need for a comprehensive course on entrepreneurship for future entrepreneurs among the University of the Philippines in the Visayas-College of Management (UPV-CM) students. A total of seventy (70) student respondents (10% of the total population) coming from the different year levels took part in the study. They were given questionnaires, which were divided into three ( 3) sections : Respondents' Characterisitics, Entrepreneurial Profile, and Entreprenuerial Test. The results of the study showed that majority of the respondent plans to put up their own business someday. However, a greater number of the respondents are classified as "journeyman" (lowest rating in the Entrepreneurial Test). Majority believed that there is a need for a comprehensive course on entrepreneurship, and that taking a comprehensive course on entrepreneurship leads to the development of entrepreneurial skills. Majority refuted the notion that " entrepreneurs are born, not made," and recognized the importance of the role education plays in a successful entrepreneurship. Analysis of the data showed that at .05 level of significance, there is a signficant need for a comprehensive course on entrepreneurship for future entrepreneurs among UPV-CM students.
Research Paper (BA 200 - Business Research) -- Iloilo City: UPV-CM, March 19, 1993.